Reltive Impact of Inflation and Unemployment on Economic Growth in Nigeria (1980-2013) - Eze, Titus Chinweuba; Eze, Peter Ikechukwu (Advances in Social Sciences Research Journal, 2015)
This study is on the quantitative analysis of the relative impact of inflation and unemployment on economic growth in Nigeria for the sample period 1980 to 2013. The econometric technique adopted for the study was multiple regression method based on ordinary least squares technique. However, in order to avoid the incidence of spurious estimates, evidence from the ADF test conducted revealed that the variables are integrated of order two,1(2). The Johansen cointegration test conducted showed evidence of long run equilibrium relationship between unemployment, inflation and gross domestic growth in Nigeria The findings revealed that the estimated longrun parameters with computed t-values of -2.605927 and -4.001583 for unemployment and inflation respectively, were highly significant at 5% levels. It also showed that both unemployment and inflation rate were inversely related with gross domestic product (GDP). The Granger causality test gave F-values of 1.94614 and 1.54103 for INF ® UNE and UNE ® INF (the arrow indicates the direction of causality) when compared with 5% theoretical F-value of 4.28. Since none of the two competed F-values was significant, the implication was that they were independent of each other. The policy recommendations therefore, are that the Central Bank of Nigeria should pursue more vigorously and transparently its policy of inflation targeting as well as reviving the energy sector to absorb millions of graduate unemployed youths.